Challenges to dietary hypertension self‐management as described by a sample of African American older adults. Issue 1 (22nd January 2022) - Jones, Lenette M.; Moss, Karen O.; Mitchell, Jamie; Still, Carolyn; Hawkins, Jaclynn; Tang, Emily; Wright, Kathy D.
Abstract: Background: Hypertension rates are disproportionately higher among Black or African Americans (Black/African American) compared to other racial and ethnic groups in the United States. However, research on self‐management strategies to control hypertension through healthy eating such as the Dietary Approaches to Stop Hypertension (DASH), and ketogenic diets has underexplored the use of dietary strategies among older Black/African American adults. In reporting contemporary challenges with implementing dietary strategies targeting blood pressure control among Black/African American older adults living with hypertension, this study addresses a clear need. Aims: Prior research has only partially addressed the challenges older Black/African Americans face in implementing and maintaining dietary strategies to control hypertension, therefore the current study aimed to address this gap by reporting contemporary challenges, as reported by a sample of Black/African American older adults living with hypertension. Methods: Nineteen Black/African American older adults living with hypertension participated in a focus group. An interview guide with open‐ended questions on dietary approaches to self‐management hypertension was used to guide data collection. Responses were audio‐recorded, transcribed verbatim, and interpreted using qualitative thematic analysis. Results: Study participants were 71.6 years ( SD = 8.3), 87.1% were women, and all were self‐identified as Black/African American. Overall, participants shared that they were interested in improving their hypertension self‐management skills. They expressed uncertainty about dietary strategies related in part to a lack of knowledge about incorporating or excluding certain foods and adhering to complex dietary recommendations. Participants also related financial concerns about accessing the recommended foods to control hypertension and expressed confusion about how to manage hypertension alongside other comorbidities. Linking Evidence to Action: This study highlights several barriers that Black/African American older adults face (lack of dietary knowledge, lack of financial resources, and unique barriers to managing multiple comorbid health conditions), which often pose simultaneous and intersecting barriers to managing hypertension using existing evidence‐based dietary strategies.